Effects of a behavioral intervention that emphasizes spices and herbs on adherence to recommended sodium intake: results of the SPICE randomized clinical trial. Issue 3 (12th August 2015) - Anderson, Cheryl AM; Cobb, Laura K; Miller, Edgar R; Woodward, Mark; Hottenstein, Annette; Chang, Alex R; Mongraw-Chaffin, Morgana; White, Karen; Charleston, Jeanne; Tanaka, Toshiko; Thomas, Letitia; Appel, Lawrence J
ABSTRACT: Background: For decades, dietary sodium intake in the United States has remained high, and few studies have examined strategies for maintaining recommended intakes. Objective: We examined the effects of a behavioral intervention, which emphasized spices and herbs, on the maintenance of sodium intake at the recommended intake of 1500 mg/d in individuals to whom the US Dietary Guidelines for Americans apply. Design: We conducted a 2-phase study that included adults ≥18 y of age for whom Dietary Guidelines for Americans recommends 1500 mg Na/d. The study was conducted in Baltimore, Maryland, from 2012 to 2014. In phase 1, 55 individuals consumed a low-sodium diet for 4 wk. Participants were provided all foods, snacks, and calorie-containing drinks. In phase 2, 40 participants from phase 1 were randomly assigned to either a behavioral intervention to reduce sodium intake ( n = 20) or a self-directed control group ( n = 20) for 20 wk. The primary study outcome was the change in mean 24-h urinary sodium excretion during phase 2. Linear regression analyses were used to determine intervention effects on urinary sodium excretion. Results: Participant characteristics were as follows: women: 65%; African American: 88%; hypertension: 63%; diabetes: 18%; mean age: 61 y; and mean body mass index (in kg/m 2 ): 30. At the end of phase 2, mean 24-h sodium excretion was lower in the behavioral intervention than in the self-directed group (mean difference: −956.8 mg/d; 95% CI: −1538.7, −374.9 mg/d) after sodium intake at screening was controlled for ( P = 0.002). These findings persisted in sensitivity analyses that excluded potentially incomplete urine collections [Mage's equation mean difference: −1090 mg/d ( P = 0.001); Joosens' equation mean difference: −796 mg/d ( P = 0.04)]. Conclusions: A multifactorial behavioral intervention emphasizing spices and herbs significantly reduced sodium intake. Because of the ubiquity of sodium in the US food supply, multilevel strategies addressing individual behaviors and the food supply are needed to improve adherence to recommendations. This trial was registered at clinicaltrials.gov as NCT01615159.